A Single-Center Retrospective Evaluation of the Use of Oral Factor Xa Inhibitors in Patients With Cerebral Venous Thrombosis. Issue 3 (March 2021) - Powell, Marissa; Tremolet de Villers, Kathryn; Schwarz, Kerry; Case, David; Trujillo, Toby
Background: Clinical practice guidelines recommend that cerebral venous thrombosis (CVT) be managed with long-term anticoagulant therapy using warfarin or low-molecular-weight heparin (LMWH) for 3 to 12 months. However, oral factor Xa inhibitors may offer preferable alternative treatment options for these patients. Objective: The primary objective was to determine the effectiveness and safety of rivaroxaban or apixaban compared with warfarin or enoxaparin as long-term anticoagulation therapy for patients with a new diagnosis of CVT. Methods: This was a single-center retrospective review of patients with newly diagnosed CVT who received acute and maintenance anticoagulation treatment. Study groups compared patients who received warfarin, enoxaparin, or an oral factor Xa inhibitor as their maintenance anticoagulant. The primary outcome was recurrent thrombotic events while on anticoagulation. Secondary outcomes included modified Rankin Scale, improved cerebral venous sinus opacification, duration of anticoagulant therapy, bleeding events during anticoagulant therapy, and adverse effects. Results: A total of 119 patients were included in the analysis: warfarin (89), enoxaparin (11), and oral factor Xa inhibitor (19). The risk of recurrent thrombotic events were 11.2%, 0%, and 10.5% in the warfarin, enoxaparin, and oral factor Xa inhibitor treatment groups, respectively ( P = 0.7635). There were no significant between-group differences observed regarding any of the secondary outcomes. Conclusions: Although the sample size is limited, these findings indicate that oral factor Xa inhibitors are a reasonable treatment option for patients with CVT. There was a trend toward more persistent symptoms in patients on warfarin, suggesting a potential improvement in recovery among patients that received an oral factor Xa inhibitor.